Dry anaerobic digestion modelling: Parameter sensitivity. (18th November 2014) - Benbelkacem, Hassen; Bollon, Julien; Gourdon, Rémy; Buffière, Pierre
Abstract A model dedicated to dry anaerobic digestion process was previously developed. This model was based on the ADM1 model and modified to take into account the specificity of dry anaerobic media. The objective of the work presented here was to study the sensitivity to the model of 2 parameters. The first parameter (kLa) was related to mass transfer of the biodegradation products (CH4, CO2, H2) from liquid phase to gas phase. Two gas production behaviours were pointed out, depending on kLa value and corresponding to limiting or non‐limiting transfer rate. A kLa value of 5 d−1 marked the transition. The second parameter (kmX) was linked to biological kinetic reactions. The sensitivity of kmX was important: a variation of ±10 % of its value affected clearly the kinetic consumption of the substrate. A method to determine those parameters was presented. This method was then used to determine both biological kinetic parameter and mass transfer coefficient from batch experimental data of methane production with acetate as organic substrate at two different moisture contents.